Witches Ways of Knowing: The Adult Learning Process in Joining Social Groups - Bradley C. Courtenay; Sharan B. Merriam; Lisa M. Baumgartner (Adult Education Research Conference, 2002)
This study explored what motivates adults to engage in learning that leads to membership in a marginalized social group and the nature of their learning process. By interviewing a sample of Wiccans, we discovered an intense internal motivation that endures over years and an integrated, holistic learning process.